Three essays on the economics of football - Özaydın, Selçuk (My University, 2020)
This thesis consists of three essays which investigate the last two decades of European football. First essay explores the distribution of income and its influence on competitive balance between the Big 5 leagues of Europe. The Gini coefficients and Lorenz curves illustrate the distortion in the revenue sharing which is adversely influential of competitive balance in favor of the English teams. Second essay discusses the impact of Financial Fair-Play regulations on European transfer market and estimates the size of the effect using a difference-in-difference estimation. The results illustrate that, the transfer activity of the leagues, which have been sanction by UEFA due to failing to meet FFP requirements, have been severely affected. Third essay investigates the social and athletic efficiencies of Turkish Super League clubs between 2012/2013 and 2017/2018 seasons using a stochastic production frontier. In both athletic and social technical efficiencies, the Big 3 of Turkey have been performing better than the others although there are occasional surprises in some seasons.

Bu tez, Avrupa futbol ekonomisini inceleyen üç makaleden oluşmaktadır. İlk makalede, Avrupa futbolunun 5 Büyük Ligi arasındaki gelir dağılımının nasıl değiştiği ve bunun rekabet dengesi üzerindeki etkisi incelenmektedir. Gini katsayısı ve Lorenz eğrilerinin gösterdiği üzere, son yıllarda gelir dağılımı bozulmaktadır ve bu da rekabet dengesinin İngiliz takımları lehine değişmesine sebep olmaktadır. İkinci makale, Finansal Fair-Play’in Avrupa transfer piyasası üzerindeki etkileri incelenmektedir. Bu bağlamda, farkların farkları (differences in differences) yöntemi kullanılarak regülasyonun etkisi tahmin edilmiştir. Tahmin sonuçları, FFP şartlarına uyamadıkları için yaptırımlarına maruz kalan liglerin, regülasyonlardan oldukça fazla etkilendiğini ortaya koymaktadır. Üçüncü makale ise, Türkiye Süper Lig takımlarının sosyal ve atletik verimliliklerini stokastik sınır analizi ile incelemektedir. Verimlilik liderlerinde, bazı sezonlarda sürpriz takımlar olmasına rağmen, hem sosyal hem atletik açıdan, 3 Büyüklerin diğer takımlardan daha verimli olduğu sonucuna varılmıştır.
Tez (Doktora) - Yıldız Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2020
Keywords: Rekabet dengesi; Gelir dağılımı; Finansal Fair-Play; Stokastik sınır analizi; Sosyal ve atletik verimlilik; Competitive balance; Distribution of income; Financial Fair-Play; Difference-in-difference; Stochastic production frontier; Social and athletic efficiency